Risk of cancer in patients with bile acid diarrhoea: a Danish nationwide matched cohort study - Tine Jess; Nynne Nyboe Andersen; Gry Poulsen; Signe Wildt; Lars Kristian Munck; Aske Thorn Iversen; Christian Borup (BMJ Open Gastroenterology)
Objective Bile acid diarrhoea is a common cause of chronic diarrhoea. Increased levels of potentially carcinogenic bile acids in faeces, theoretically, may increase the risk of colorectal cancer in particular, but the long-term disease course is unknown. We aimed to investigate the overall and site-specific cancer risk in bile acid diarrhoea.Design Adult patients with bile acid diarrhoea were identified using nationwide Danish registries from 2003 to 2020 by a diagnostic gold-standard 75-selenium tauroselcholic acid procedure followed within 6 months by sequestrant prescription. The risk of overall and site-specific cancers in cases with bile acid diarrhoea was compared with sex, age and comorbidity-adjusted matched controls. A competing risk model estimated cumulative incidence functions and cause-specific HRs.Results We identified 2260 patients with bile acid diarrhoea with a mean follow-up of 5.5 years (SD 4.2). The overall cancer risk was increased by an HR of 1.32 (95% CI 1.12 to 1.54). The risk of site-specific cancer was increased in 3 of 10 cancer groups: haematological, HR 2.41 (1.36 to 4.02); skin, HR 1.33 (1.01 to 1.71); and male genital cancers, HR 1.85 (1.11 to 2.92). No increased risk of colorectal cancer was detected in patients with bile acid diarrhoea, HR 0.73 (0.34 to 1.63).Conclusions Bile acid diarrhoea was associated with an increased overall risk of cancer, especially haematological cancers, but the risk of colorectal cancer was not increased. The lack of a diagnostic code for bile acid diarrhoea and potential residual confounding are limitations, and the findings should be replicated in other cohorts.